The impact of sustainable entrepreneurship education and self-efficacy on students' entrepreneurial mindset and attitude - Wiyanto, Hendra; Widayati, Catur (Edelweiss Applied Science and Technology, 2024)
This study aims to foster a shift in students' entrepreneurial mindset through sustainable entrepreneurship education. This initiative is expected to contribute to the recovery of the MSME (Micro, Small, and Medium Enterprises) sector while enhancing the quality of education by expanding the content of entrepreneurship courses, inviting experts to share their experiences, organizing events to promote student products, and facilitating internships in the entrepreneurial industry. Data were collected through questionnaires, with responses measured using a Likert scale. A literature review was also conducted to support the research. The population of this study consists of students from universities in West Jakarta, with a sample of 153 respondents. The data were analyzed using a structural equation modeling approach based on components or variances. The results of hypothesis testing reveal that: (1) Entrepreneurship education has a positive and significant effect on the entrepreneurial mindset; (2) Self-efficacy has a positive and significant effect on the entrepreneurial mindset; (3) Entrepreneurship education has a positive and significant effect on entrepreneurial attitude; (4) Self-efficacy has a positive and significant effect on entrepreneurial attitude; (5) Entrepreneurial attitude has a positive and significant effect on the entrepreneurial mindset; (6) Entrepreneurial attitude does not mediate the relationship between entrepreneurship education and entrepreneurial mindset; and (7) Entrepreneurial attitude does not mediate the relationship between self-efficacy and entrepreneurial mindset.